2018
DOI: 10.1002/asi.24066
|View full text |Cite
|
Sign up to set email alerts
|

A Discussion of citations from the perspective of the contribution of the cited paper to the citing paper

Abstract: To more reasonably allocate a paper's credit, this article argues that both a paper's authors and references contribute to a given paper. Accordingly, we quantitatively represent the proportion of contributions from each author and reference to a paper. A paper's credit can be allocated among its authors and references based on their contributions. All papers carry innate credit because of publication. If cited, they also carry external credit from the citing papers. The proportion of a paper's credit allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In this paper, we found that, in the field of computational linguistics, citations from Introduction and Method at the early stage of citation lifetime are particularly important for measuring the future impact of papers. Indeed, papers cited in Introduction tend to serve as illustrating the motivation and research problems (Ding et al, 2013; Lu et al, 2018), and are more likely to be pioneers of research issues or state of the art for the research question, and have thus inspired the author(s) to carry out the research work (Fang, 2018). The papers frequently cited in Method tend to be methodology‐oriented papers (Hu et al, 2013), and are especially important in computational linguistics, as they provide methodological trajectories (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we found that, in the field of computational linguistics, citations from Introduction and Method at the early stage of citation lifetime are particularly important for measuring the future impact of papers. Indeed, papers cited in Introduction tend to serve as illustrating the motivation and research problems (Ding et al, 2013; Lu et al, 2018), and are more likely to be pioneers of research issues or state of the art for the research question, and have thus inspired the author(s) to carry out the research work (Fang, 2018). The papers frequently cited in Method tend to be methodology‐oriented papers (Hu et al, 2013), and are especially important in computational linguistics, as they provide methodological trajectories (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As it was previously mentioned, the half-life parameter (A) is not the same for different disciplines. For publications in the field of mathematics, scholars have made estimations on their half-life (Fang, 2018;Zhong et al, 2011). They reported that publications in this field have a long half-life comparing to others.…”
Section: Parameter Settingsmentioning
confidence: 99%